Metabolomics of the interaction between PPAR‐α and age in the PPAR‐α‐null mouse - Helen J Atherton; Melanie K Gulston; Nigel J Bailey; Kian‐Kai Cheng; Wen Zhang; Kieran Clarke; Julian L Griffin (Molecular Systems Biology)
Abstract Regulation between the fed and fasted states in mammals is partially controlled by peroxisome proliferator‐activated receptor‐α (PPAR‐α). Expression of the receptor is high in the liver, heart and skeletal muscle, but decreases with age. A combined 1H nuclear magnetic resonance (NMR) spectroscopy and gas chromatography‐mass spectrometry metabolomic approach has been used to examine metabolism in the liver, heart, skeletal muscle and adipose tissue in PPAR‐α‐null mice and wild‐type controls during ageing between 3 and 13 months. For the PPAR‐α‐null mouse, multivariate statistics highlighted hepatic steatosis, reductions in the concentrations of glucose and glycogen in both the liver and muscle tissue, and profound changes in lipid metabolism in each tissue, reflecting known expression targets of the PPAR‐α receptor. Hepatic glycogen and glucose also decreased with age for both genotypes. These findings indicate the development of age‐related hepatic steatosis in the PPAR‐α‐null mouse, with the normal metabolic changes associated with ageing exacerbating changes associated with genotype. Furthermore, the combined metabolomic and multivariate statistics approach provides a robust method for examining the interaction between age and genotype.